METAPHOR LANGUAGE PORTRAYED IN THE CULTURAL ASSIMILATION IN THE NOVEL THE VALENTINE HOUSE BY EMMA HENDERSON - Andarista, Amalia Elara; Panggabean, Waladdin (Prologue: Journal on Language and Literature, 2024)
This study explores the metaphor language portrayed in the cultural assimilation in the novel The Valentine House by Emma Henderson. There are two objectives of this research; 1) To find the types of metaphor language found in the novel "The Valentine House" by Emma Henderson, and 2) To explain the metaphor language that describes cultural assimilation in the novel "The Valentine House" by Emma Henderson. In analyzing the data, the researcher uses the theory of Metaphor by Aristoteles to find out the forms of metaphor language contained in the novel, then the researcher analyzes and explains the data from the novel. The methodology in this study is qualitative research by taking data from quotations in the novel which the researcher then conveys descriptively. The results of this study, the researchers found that the types of metaphor language in the novel The Valentine House by Emma Henderson are standard metaphor, implied metaphor, visual metaphor, and extended metaphor. And the metaphor language that is described in the cultural assimilation that affects the metaphor language is culture as an idea and culture as an activity.